Homoafetividade e direitos: repertórios discursivos construídos no âmbito jurídico - Lima, Raquel Moraes de (2014)
This doctoral thesis aims at investigating the ways in which the discursive repertoires on same-sex relationships and the rights of sexual minorities are formed in the legal scope. In May 2011, the Supremo Tribunal Federal (Brazilian Supreme Court), in an unprecedented verdict, recognized same-sex unions as family entity, which set new directions to the homosexual movements in Brazil. Although STF s decision indicates a paradigm shift, it is noticeable that unfavorable notions on same-sex relationships and the rights of sexual minorities are still being spread throughout society. In this sense, trying to delineate how law and legal institutions have contributed to the emancipatory processes of the sexual minorities, the discursive repertoires produced in two legal spheres have been analyzed. Those spheres are namely the STF and the academic legal community, which have influenced to a large extent the ways in which the law and society are conceived. In the first study, lexical (ALCESTE) and textual analyses (critical discourse analysis) showed the similarities and differences between the arguments and justifications used by the STF ministers during the pronouncement of their favorable votes to the recognition of same-sex unions. It has been verified the existence of discursive repertoires that vary from the acceptance and recognition of equality to the idea of tolerance (stand with indulgence), supported by the emphasis on differences. From the results collected in the analysis of the STF ministers votes, a questionnaire, marked by objective and essay questions, was elaborated, in order to progress to two more studies (second and third), which were directed to students and professors of the law course at Universidade Federal da Paraíba. In the second study, students and professors opinions were evaluated in relation to three questions: STF ministers justifications; legal, moral, political and social consequences created by the verdict; possible factors to explain homosexuality. In relation to the STF ministers justifications, a lexical analysis proved the existence of discursive repertoires that, even though they reproduce many antagonisms in the STF ministers decision, they did not present in their content the discourse of tolerance. Regarding the consequences created by the verdict, a bigger percentage of repertoires that highlighted the decision as a legal event that helped the social inclusion of sexual minorities may be pointed out. As for the possible factors which can explain homosexuality, the majority of discursive repertoires highlighted the idea that it is a sexual orientation as any other, not a disease. In the third study, it was observed the importance of the insertion in different social groups in the students and professors opinions on those questions, from psychosocial factors: position in the educational process (student or professor), sex, marital status, and religion. The results from the cross-frequency analyses by Pearson s chi-squared test (χ²) indicated that the different social positions of the individuals influenced their visions on the questions asked, especially in what concerns religion. In conclusion, it may be affirmed that, in Brazilian contemporary scenario, the jurisprudential decisions have become important mechanisms to put into effect the rights of minority groups, in a sense that the formation of legal professionals seems to have become increasingly significant when it comes to deconstructing the processes of social inequality.